PENYELENGGARAAN PENDIDIKAN DALAM MEMBENTUK KARAKTER RELIGIUS SISWA SMK AL-QUR’AN DAN DAKWAH ALAM - Assidiqi, Rahmad; sukoco, Sukoco; Hadi, Agustinus Sutriyanto (Journal of Democratia, 2025)
Education is a process of knowledge transformation that involves various aspects and components to support comprehensive learning activities. However, the current education system is considered to place excessive emphasis on cognitive aspects, thus falling short in shaping students’ moral character holistically. This is reflected in the widespread phenomenon of juvenile delinquency, which indicates a weak internalization of character values. As a response, character-based education has been implemented as a solution to foster students' morality. This study aims to explore the behavior of students at SMK Al-Qur’an and Dakwah Alam in the process of instilling religious character. Specifically, the study seeks to describe the implementation of religious character education and to identify the supporting and inhibiting factors in this process. The research employs a qualitative approach with a phenomenological design. The findings indicate that the implementation of religious character education at SMK Al-Qur’an and Dakwah Alam has been fairly effective. However, several challenges remain, including limited understanding of religious character values and insufficient training and socialization provided by relevant stakeholders. Consequently, religious character education is still predominantly found in religious institutions such as Islamic boarding schools (pesantren). The study concludes that the success of religious character education requires collaboration from all parties—not only teachers but also all elements of the education system, including the government. Teachers are expected to apply various instructional methods to ensure a more effective and contextual character education process. Keywords: Religious, character, education